On the maximum of generalized stirling numbers - Corcino, Roberto B.,; Corcino, Cristina B., (Utilitas Mathematica, 2011)
The value of the index for which the sequence of generalized Stirling numbers of the first and second kinds assume their maximum values, is determined.